Development of Using Blended Learning Education-Based Game Learning Media Android for Students Basic Electronics - Hendro Welas Setiawan; Muchlas Muchlas (Journal of Vocational Education Studies, 2021)
The objectives of this study were to: (1) develop a blended learning model using Android-based learning media for basic electrical electronics subjects; and (2) determine the effectiveness and level of student satisfaction with the developed model. This study used the Research and Development method with the ADDIE development model which consisted of defining, designing, developing, implementing and evaluating stages. The research subjects consisted of 2 media expert validators, 2 material expert validators, and 31 product trial students. The research instrument used a questionnaire for media experts and material experts, as well as tests and questionnaires for students. The level of student satisfaction with the developed model was determined by the percentage technique, while the product testing was carried out with an experimental design (before-after) and a one group pretest-posttest pattern. This study produces a blended learning model using educational game media based on android for basic electrical electronics subjects. The results showed that the product developed obtained a validity score of 82.5% from media experts who were on valid criteria and a score of 93.7% from material experts was in very valid criteria. The model developed can be used effectively for basic learning of electronic electricity in vocational schools, which is shown by the post-test average score of 80.97, which is higher than the pre-test average score of 64.09. The level of student satisfaction with the product developed was very good with an average score of 85.8 on a scale of 100.